2020
DOI: 10.1016/j.molmet.2020.101076
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of donor feces affects the gut–brain axis in humans with metabolic syndrome

Abstract: Objective Increasing evidence indicates that intestinal microbiota play a role in diverse metabolic processes via intestinal butyrate production. Human bariatric surgery data suggest that the gut-brain axis is also involved in this process, but the underlying mechanisms remain unknown. Methods We compared the effect of fecal microbiota transfer (FMT) from post-Roux-en-Y gastric bypass (RYGB) donors vs oral butyrate supplementation on ( 123 I-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 104 publications
2
84
0
6
Order By: Relevance
“…So far, no studies have investigated the effect of FMT in AD patients. However, an effect of FMT on the brain was demonstrated in obese patients, where FMT increased dopamine transporter binding which was associated with an concomitant increase in Bacteroides uniformis ( 174 ).…”
Section: Therapeutic Strategies Targeting the Gut Microbiota And Metabolites In Admentioning
confidence: 99%
“…So far, no studies have investigated the effect of FMT in AD patients. However, an effect of FMT on the brain was demonstrated in obese patients, where FMT increased dopamine transporter binding which was associated with an concomitant increase in Bacteroides uniformis ( 174 ).…”
Section: Therapeutic Strategies Targeting the Gut Microbiota And Metabolites In Admentioning
confidence: 99%
“…This is important as adverse metabolic traits can be transferred (de Groot et al, 2020a). In this regard, it is also likely that the metabolic phenotype of the FMT donor can affect gut-brain axis in human subjects (Hartstra et al, 2020).…”
Section: Review Fmts In Metabolic Conditionsmentioning
confidence: 99%
“…It is also increasingly appreciated that gut microbes may produce a range of metabolites that alter human behaviors, either directly by metabolites that pass the blood-brain barrier, or indirectly through modulation of the autonomous nervous activity of the gut leading to altered satiety and mood. FMTs may therefore target the gut-brain axis (Figure 4F), regulating metabolites associated with mood and satiety, key players in the development of insulin resistance (Hartstra et al, 2020).…”
Section: Llmentioning
confidence: 99%
“…Furthermore, ex vivo treatment of human adipose tissue biopsies with propionic acid increased the expression of the anorexigenic hormone leptin and reduced inflammatory factors [ 78 , 79 ]. Most studies in humans are associative, and our group recently showed that oral administration of SCFA butyrate does not improve glucose metabolism or vagal tone in metabolic syndrome subjects [ 76 , 80 ]. Additional human trials are needed to further identify the possible role of other SCFAs as intervention in obesity and obesity-related metabolic disorders.…”
Section: The Microbiota–gut–brain Axismentioning
confidence: 99%
“…The role of serotonin in obesity is complex, and the role the microbiota have on central serotonin is still unclear. However, our recent pilot study using SPECT imaging in humans suggested that the gut microbiota can directly or indirectly affect brain serotonin (and dopamine) transporter binding potential in humans with obesity via sympathetic tone [ 80 ].…”
Section: Other Neurotransmittersmentioning
confidence: 99%